Pendidikan Islam K.H. Abdul Halim Sintesis Fungsi Teologis dan Sosiologis Pendidikan Islam - caswita caswita (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2021)
This research is motivated by the importance of morality/akhlakul karimah and skills/work skills for graduates of Islamic education. One of the leading thinkers of Islamic education, K.H Abdul Halim, tried to synthesize the functions of Islamic education between theological and sociological ones. The purpose of this research is to explore the thoughts of Islamic education figure K.H Abdul Halim how should Islamic education occur a synthesis between theological and sociological functions. This research method is library research. In library research, it is done by writing, clarifying, reducing, and presenting data from various written sources. The results of the study show that the thoughts of Islamic education leaders K, H Abdul Halim are still very relevant to be applied at this time, namely producing educational outputs that have good morals and have work skills.